Pemanfaatan Media Fitur Reels Instagram Dalam Kreativitas Menulis Puisi - Rifa Salsabila (LPPM Politeknik Pratama, 2023)
A complex process that occurs in everyone and lasts a lifetime is learning because knowledge can be obtained by all people, as well as with the current development of technology. The world offers various conveniences in finding information from various lines. The use of social media is a way to make it easier for users to find information and disseminate information, including creativity in writing poetry. Creativity in writing poetry can be seen in the ability of individuals to express themselves. One social media that is widely used by all people today is Instagram. This research is a qualitative research using a descriptive method, namely describing what is in accordance with the features on Instagram. There are many features on Instagram, the author chooses the reels feature to increase creativity in writing poetry. The purpose of this research is because the use of the Instagram reels feature has images, video, audio, text that can be changed as needed, this will make it easier to use Instagram reels to increase creativity in writing poetry.